6x+12=-9x-16

Simple and best practice solution for 6x+12=-9x-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+12=-9x-16 equation:


Simplifying
6x + 12 = -9x + -16

Reorder the terms:
12 + 6x = -9x + -16

Reorder the terms:
12 + 6x = -16 + -9x

Solving
12 + 6x = -16 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
12 + 6x + 9x = -16 + -9x + 9x

Combine like terms: 6x + 9x = 15x
12 + 15x = -16 + -9x + 9x

Combine like terms: -9x + 9x = 0
12 + 15x = -16 + 0
12 + 15x = -16

Add '-12' to each side of the equation.
12 + -12 + 15x = -16 + -12

Combine like terms: 12 + -12 = 0
0 + 15x = -16 + -12
15x = -16 + -12

Combine like terms: -16 + -12 = -28
15x = -28

Divide each side by '15'.
x = -1.866666667

Simplifying
x = -1.866666667

See similar equations:

| -12.3f=73.8 | | k^2-7k+20=8 | | b+53=75 | | 1/3x-7=20 | | v-7=36 | | 1/3n-8=-13 | | 5x+33=3x+6 | | ln(x-3)-lnx=ln(2/7) | | 0.5(4t+24)=22t-2 | | ln(sinx)=-ln(secx) | | 5c+3c=72 | | 5a-2a=6 | | 3c^2-4x-4=0 | | 10/13/4/9 | | 5a-2whena=6 | | 3x-3=8x+2 | | 2x+14=-8x+14 | | 5x+6x-8=180 | | 2e=3e+36 | | 8x^3+18x^2+10x=0 | | 9x-13x=12 | | 2w/7=56 | | W(w+3)=96 | | 28m^2-100m-48=0 | | 3y+5x-10=2x+8y+9 | | 115+2x+x+115=180 | | a+2+c+5+e=db | | N^2+10n-7=-6 | | (4+b)*(A+C)=5 | | 5b^2+16b-16=0 | | 72+2x+x+47.5=180 | | 3/4x=20tx |

Equations solver categories